Perlindungan Hukum Terhadap Pemilik Hak Atas Tanah Akibat Terjadinya Sertipikat Ganda - Ulfa, Monalisa (Zaaken: Journal of Civil and Business Law, 2022)
This study aims to determine and analyze the causes of the occurrence of double certificates at the Jambi City Land Office and the form of legal protection for land rights owners due to the occurrence of double certificates at the Jambi City Land Office. The formulation of the problems raised are 1) what is the cause of the occurrence of double certificates at the Jambi City Land Office; 2) what is the form of legal protection for the owner of land rights due to the occurrence of double certificates at the Jambi City Land Office. The method used is the type of empirical juridical research. The results showed that 1) the occurrence of double certificates at the Jambi City Land Office was caused by factors, the Jambi City Land Office in the form of errors in measurement, officials did not check whether there were certificates of ownership rights on land before, were not careful in checking physical data and juridical data, there is no land map, the principle of elimination of contradictions is not applied and there is no announcement at the village office for 60 days. As for the parties in the form of incorrectly appointing the land boundary and domicile of one of the parties outside the city; 2) the form of legal protection for the owner of land rights due to the occurrence of double certificates at the Jambi City Land Office, efforts are made for each Land Office to provide land registration maps; through controlling the land registration process and through administrative controls related to land in the kelurahan. Abstrak Penelitian ini bertujuan untuk mengetahui dan menganalisis penyebab terjadinya sertipikat ganda di Kantor Pertanahan Kota Jambi dan bentuk perlindungan hukum terhadap pemilik hak atas tanah akibat terjadinya sertipikat ganda di Kantor Pertanahan Kota Jambi. Perumusan masalah yang diangkat yaitu 1) bagaimana penyebab terjadinya sertipikat ganda di Kantor Pertanahan Kota Jambi; 2) bagaimana bentuk perlindungan hukum terhadap pemilik hak atas tanah akibat terjadinya sertipikat ganda di Kantor Pertanahan Kota Jambi. Metode yang digunakan adalah tipe penelitian yuridis empiris. Hasil penelitian menunjukkan bahwa 1) terjadinya sertipikat ganda di Kantor Pertanahan Kota Jambi disebabkan oleh faktor-faktor, Kantor Pertanahan Kota Jambi berupa kesalahan dalam pengukuran, pejabat tidak memeriksa ada tidaknya sertipikat hak milik atas tanah sebelumnya, kurang teliti memeriksa data fisik dan data yuridis, tidak adanya peta tanah, tidak diterapkannya asas deliminasi kontradiktur dan tidak dilakukannya pengumuman di kantor desa selama 60 hari. Sedangkan untuk para pihak berupa salah menunjuk batas tanah dan domisili salah satu pihak di luar kota; 2) bentuk perlindungan hukum terhadap pemilik hak atas tanah akibat terjadinya sertipikat ganda di Kantor Pertanahan Kota Jambi dilakukannya upaya tiap-tiap Kantor Pertanahan harus menyediakan peta pendaftaran tanah; melalui penertiban proses pendaftaran tanah dan melalui penertiban administrasi terkait dengan pertanahan di kelurahan. Â